Increased left ventricular mass in a bodybuilder using anabolic steroids. Issue 4 (December 1986) - McKillop, G; Todd, I C; Ballantyne, D
Abstract : As the effects of anabolic steroids on left ventricular structure and function are unknown, we carried out clinical examination, 12 lead electrocardiography and echocardiography on a 23 year old male bodybuilder using these drugs. In this subject we found values of ECG voltage criteria, left ventricular-mass, posterior wall and interventricular septal thickness which exceeded those found in normal subjects and also in other competitive, power athletes. Despite these values, however, ejection fraction remained normal. This would suggest that anabolic steroids perhaps have a direct effect on the myocardium, in addition to the effects of training, but whether this is of pathological significance is unclear.